2003
DOI: 10.1557/jmr.2003.0355
|View full text |Cite
|
Sign up to set email alerts
|

Electromigration failure in flip chip solder joints due to rapid dissolution of copper

Abstract: An electromigration failure mechanism in flip chip solder joints is reported in this communication. The solder joints failed by a very rapid, asymmetrical, and localized dissolution of the Cu metallization on the cathode side. The average dissolution rate was about 1 μm/min. The dissolved Cu included not only the Cu under bump metallurgy but also the on-chip Cu conducting trace. From the location and geometry of the dissolved Cu, it can be concluded that current crowding plays a critical role in the rapid diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(64 citation statements)
references
References 12 publications
1
57
1
1
Order By: Relevance
“…This are was believed to have the highest local current density and the highest degree of current crowding initially. [2][3][4][5][6][7][8][9][10] Figure 5 is a zoom-in image for the left side of the void shown in Fig. 2b.…”
Section: Osp Surface Finishmentioning
confidence: 99%
See 1 more Smart Citation
“…This are was believed to have the highest local current density and the highest degree of current crowding initially. [2][3][4][5][6][7][8][9][10] Figure 5 is a zoom-in image for the left side of the void shown in Fig. 2b.…”
Section: Osp Surface Finishmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] To counter the negative effects caused by high current density, several approaches have been proposed and deployed. Two well-known approaches involve better circuit and interconnect designs.…”
Section: Introductionmentioning
confidence: 99%
“…Цей процес також супроводжується утворенням пор на катоді між ІМС та циною. Таким чином катода поступово розчиняється в цині, а атоми Cu з нього приймають участь у рості ІМС на аноді [19,20]. В нашому експерименті таке перенесення неможливе, але результат залишається незмінним.…”
Section: результати експерименту та їх обговоренняunclassified
“…3 Relevant studies indicate that electromigration can induce significant microstructural changes and different intermetallic growth in the solder joint systems. [4][5][6][7][8][9][10][11][12][13] The microstructural changes include void nucleation and propagation, hillock formation, and phase segregation. In the eutectic SnPb solder, it was found that electromigration could force Pb atoms to migrate along the direction of electron flow and accumulate at the anode side.…”
Section: Introductionmentioning
confidence: 99%